Evaluation of Cinnamon Supplementation on Insulin Resistance, BMI and Estradiol Levels in Women with Polycystic Ovary Syndrome: A Double-Blinded Randomized Controlled Clinical Trial - Anahita Nazempour; AboTaleb Saremi; Nasrin hakak; Shamsali Rezazadeh; Saeideh Momtaz (Journal of Women's Reproductive Health, 2022)
Background Polycystic ovary syndrome (PCOS) is a serious multifactorial disorder. This study intended to assess the effect of cinnamon supplementation on estradiol level, and fasting- and two-hour (2 hpp) insulin and sugar levels in women with PCOS. Material and Methods This study was a double-blinded randomized clinical trial (RCT), conducted between January 2019 until December 2020, at Gynecology Clinic Sarem Women’s Hospital in Tehran, Iran. Patients with PCOS, 130 subjects (65 person/ group) were diagnosed using Rotterdam diagnostic criteria. All participants received daily treatment consisting of 1500 mg metformin and 1000 mg cinnamon per day for 12 weeks. An evaluation of serum AMH level was conducted before and after the completion of therapy. Results Cinnamon supplementation significantly reduced the estradiol, fasting glucose and 2hpp glucose, fasting insulin and 2 hpp insulin, BMI and weight levels after intervention. The highest reduction was observed in fasting glucose, 2 hpp insulin, and estradiol groups after intervention (P<0.05). There was a significant difference between the means of BMI (P<0.01), fasting sugar (P<0.01), and 2 hpp glucose (P<0.01) before and after intervention. Conclusion Cinnamon supplementation, as a safe herbal product, can be prescribed with metformin to improve the symptoms and complications of PCOS.
Keywords: Polycystic ovary syndrome (PCOS)